Tissue Culture—A Sustainable Approach to Explore Plant Stresses - Akila Wijerathna-Yapa; Jayeni Hiti-Bandaralage (Life, 2023)
Plants are constantly faced with biotic or abiotic stress, which affects their growth and development. Yield reduction due to biotic and abiotic stresses on economically important crop species causes substantial economic loss at a global level. Breeding for stress tolerance to create elite and superior genotypes has been a common practice for many decades, and plant tissue culture can be an efficient and cost-effective method. Tissue culture is a valuable tool to develop stress tolerance, screen stress tolerance, and elucidate physiological and biochemical changes during stress. In vitro selection carried out under controlled environment conditions in confined spaces is highly effective and cheaper to maintain. This review emphasizes the relevance of plant tissue culture for screening major abiotic stresses, drought, and salinity, and the development of disease resistance. Further emphasis is given to screening metal hyperaccumulators and transgenic technological applications for stress tolerance.